Probing thoracic dose patterns associated to pericardial effusion and mortality in patients treated with photons and protons for locally advanced non-small-cell lung cancer. (July 2021) - Cella, Laura; Monti, Serena; Xu, Ting; Liuzzi, Raffaele; Stanzione, Arnaldo; Durante, Marco; Mohan, Radhe; Liao, Zhongxing; Palma, Giuseppe
Highlights: A wide range of dosimetric parameters have been associated to pericardial effusion (PCE) development and worse overall survival (OS) after thoracic irradiation. Conflicting results have been reported on the relationship between PCE and OS. We investigate by voxel-based analysis (VBA) the dose–response patterns for PCE and OS in patients treated with photon or protons for locally advanced Non-Small-Cell Lung Cancer. The robustness of VBA results was assessed by a novel characterization of spatial properties of dose distributions based on probabilistic independent component analysis (PICA) and connectograms. VBAs highlighted largely overlapping clusters significantly associated with PCE endpoints in the heart and in the lungs, while no association between PCE and OS was found. Abstract: Purpose: To investigate thoracic dose–response patterns for pericardial effusion (PCE) and mortality in patients treated for locally advanced Non-Small-Cell Lung Cancer (NSCLC) by Intensity Modulated RT (IMRT) or Passive-Scattering Proton Therapy (PSPT). Methods: Among 178 patients, 43.5% developed grade ≥ 2 PCE. Clinical and dosimetric factors associated with PCE or overall survival (OS) were identified via multi-variable Cox proportional hazards modeling. The Voxel-Based Analyses (VBAs) of local dose differences between patients with and without PCE and mortality was performed. The robustness of VBA results was assessed by a novel characterization of spatial properties of dose distributions based on probabilistic independent component analysis (PICA) and connectograms. Results: Several non-dosimetric variables were selected by the multivariable analysis for the considered outcomes, while the time-dependent PCE onset was uncorrelated with the OS ( p  = 0.34) at a multi-variable Cox analysis. Despite the significant PSPT dosimetric advantage, the RT technique did not affect the occurrence of PCE or OS. VBAs highlighted largely overlapping clusters significantly associated with PCE endpoints in heart and lungs. No significant dosimetric patterns related to mortality endpoints were found. PICA identified 43 components homogeneously scattered within thorax, while connectograms showed modest correlations between doses in main cardio-pulmonary substructures. Conclusions: Spatially resolved analysis highlighted dose patterns related to radiation-induced cardiac toxiciy and the observed organ-based dose–response mismatch in PSPT and IMRT. Indeed, the thoracic regions spared by PSPT poorly overlapped with the areas involved in PCE development, as highlited by VBA. PICA and connectograms proved valuable tools for assessing the robusteness of obtained VBA inferences.